Legal Analysis of Communal Rights of Ammatoa Kajang Customary Law Community On Customary Forest In Bulukumba District - Ade Putra Frima Sumbara (PT Publikasiku Academic Solution, 2023)
This study aims to find out the implementation of the communal rights of the Ammato Kajang customary law community in the customary forest in the Bulukumba district and to find out to what extent the communal rights of the Ammatoa Kajang customary law community are protected by law. The research method used is Normative Law research. The results showed that the implementation of the communal rights of the Ammatoa Kajang indigenous people was carried out on the authority of the Ammatoa based on